Brain-wide neuron quantification toolkit reveals strong sexual dimorphism in the evolution of fear memory - Alessandra Franceschini; Giacomo Mazzamuto; Curzio Checcucci; Lorenzo Chicchi; Duccio Fanelli; Irene Costantini; Maria Beatrice Passani; Bianca Ambrogina Silva; Francesco Saverio Pavone; Ludovico Silvestri (Cell Reports, 2023)
Summary: Fear responses are functionally adaptive behaviors that are strengthened as memories. Indeed, detailed knowledge of the neural circuitry modulating fear memory could be the turning point for the comprehension of this emotion and its pathological states. A comprehensive understanding of the circuits mediating memory encoding, consolidation, and retrieval presents the fundamental technological challenge of analyzing activity in the entire brain with single-neuron resolution. In this context, we develop the brain-wide neuron quantification toolkit (BRANT) for mapping whole-brain neuronal activation at micron-scale resolution, combining tissue clearing, high-resolution light-sheet microscopy, and automated image analysis. The robustness and scalability of this method allow us to quantify the evolution of activity patterns across multiple phases of memory in mice. This approach highlights a strong sexual dimorphism in recruited circuits, which has no counterpart in the behavior. The methodology presented here paves the way for a comprehensive characterization of the evolution of fear memory.